Pengembangan Lembar Kerja Matematika Berbasis Pemecahan Masalah Kelas VIII Di SMPN 2 Rembang, Purbalingga, Jawa Tengah - Naimah, Khusnul, Prof. Markhamah, M.Hum, Idris Harta, M.A., Ph.D (2016)
It is our duty as teacher to make student's love at mathematics thereby one with substance learn as tool. This study aims to: (1) describe the worksheet of mathematics which use the teacher in this time and describe the fungtion, (2) development the worksheet of mathematics base on problem solving, (3) examined effectiveness from the worksheet of mathematics which base on problem solving in mathematics lessons grade VIII. Method which use is Research and Development with Sukmadinata's groove which are : (1) preliminary study consisting of: literature study, instrument stack, field surveys, and compile the product's draft; (2) the develop withe steps: limited trial and first revision then extensive trial and second revision; (3) the trial with step: pretest, treatment, posttest. Result of this study: (1) worksheet of mathematics which used techer not base on problem solving, the fungtion as question's source, (2) worksheet of mathematics base problem solving have contents activity to find the concept of circle material and problem solve's questions about routine task and non routine task, (3) worksheet of mathematics base problem solving which used in mathematics lesson at grade VIII have effectiveness because there is difference between before and after apply the product, but study outcomes not yet maximum because the student who pass is 8,82% in limited trial and 32,35% in extensive trial.